Equity capital, bankruptcy risk and the liquidity trap - Oren Levintal (Bar-Ilan University, Department of Economics, 2011)
This paper explains the emergence of liquidity traps in the aftermath of large-scale financial crises, as happened in the US 1930s, Japan 1990s and recently in the US and Europe. The paper introduces a new balance sheet channel that links equity capital to the risk-free interest rate. When equity capital falls, bankruptcy risks rise. Firms become more vulnerable to external shocks, which makes financial disasters more likely to happen. Consequently, demand for safe assets increases, and the interest rate falls to the lower bound. Simulations show that the interest rate may stay at the lower bound for a long time.
Keywords: E32; E43; E44; E52; G12; G32; 330; liquidity trap; financial crisis; rare disasters; equity capital; leverage; bankruptcy risk; Liquidität; Finanzkrise; Liquiditätsbeschränkung; Schock; Eigenkapital; Insolvenz; Risiko; USA; Japan; Europa